Association of Composite Dietary Antioxidant Index With the Risk of Nonalcoholic Fatty Liver Disease and All-Cause and Cause-Specific Mortality: Evidence From NHANES 2001–2018 - Yingchao Ding; Miaomiao Fan; Chen Jiang; Naixin Dou; Yaqi Guo; Xiaolin Zhao; Xin Sun; Chunxiao Yu; Qingbo Guan (International Journal of Endocrinology)
Evidence regarding the associations of composite dietary antioxidant index (CDAI) with the risk of prevalence and mortality of nonalcoholic fatty liver disease (NAFLD) is limited. We aimed to investigate these relationships using data from the National Health and Nutrition Examination Survey (NHANES). A total of 19,404 individuals with a mean age of 50.10 years were included. In multivariate-adjusted logistic regression analysis, compared to those in the lowest quartile of CDAI, individuals with the highest quartile were negatively associated with NAFLD prevalence (OR: 0.85, 95% CI: 0.75, 0.96), and the dose–response curve exhibited a linear relationship. Moreover, multivariate-adjusted Cox regression revealed that individuals with the highest quartile were negatively associated with cancer mortality (HR: 0.61, 95% CI: 0.37, 0.99) compared to those with the lowest quartile of CDAI in NAFLD patients. Moreover, the dose–response analysis demonstrated that CDAI had a nonlinear association with all-cause mortality in NAFLD patients. Multiple stratified and sensitivity analyses demonstrated that these associations are stable. CDAI was protective against the prevalence and cancer mortality of NAFLD. These results may provide new insights into adapting CDAI as a dietary strategy to prevent and improve the prognosis of NAFLD.